Prognostic Influence of Spontaneous Tumor Rupture in Patients With Hepatocellular Carcinoma After Hepatectomy: A Meta-Analysis of Observational Studies - Xu, Jiaxuan; Hong, Jiaze; Wang, Yiran; Zhou, Lingling; Xu, Binbin; Si, Yuexiu; He, Yujing; Chen, Yizhou (Frontiers in Surgery, 2021)
Objective: This study aims to comprehensively analyze the influence of spontaneous tumor rupture on the prognosis of hepatocellular carcinoma patients following hepatic resection. Methods: We systematically searched four online electronic databases, including PubMed, Embase, Web of Science, and Cochrane Library, for eligible studies published from inception to March 2021. The main endpoints were overall survival (OS) and disease-free survival (DFS). Results: This meta-analysis included 21 observational articles with 57241 cases. The results revealed that spontaneous tumor rupture was associated with worse OS (hazard ratio (HR), 1.65; 95% confidence interval (CI), 1.33-2.05) and DFS (HR, 1.42; 95% CI, 1.12-1.80) in resectable hepatocellular carcinoma patients. This phenomenon was observed in most subgroups, which were classified by recorded survival time, age, country, alpha-fetoprotein (AFP) concentration, liver cirrhosis, and microvascular invasion. However, in subgroups of macrovascular invasion positive, spontaneous tumor rupture was not a risk factor for OS (HR, 1.55; 95% CI, 0.99-2.42) and DFS (HR, 1.23; 95% CI, 0.91-1.65) in hepatocellular carcinoma patients after hepatectomy. For macrovascular invasion negative, compared with non-ruptured hepatocellular carcinoma patients, ruptured hepatocellular carcinoma patients exhibited worse prognosis for OS (HR, 1.55; 95% CI, 0.99-2.42) and DFS (HR, 1.23; 95% CI, 0.91-1.65) following hepatectomy. Conclusions: Spontaneous tumor rupture was a prognostic risk factor for hepatocellular carcinoma patients after hepatic resection. However, in macrovascular invasion patients, spontaneous tumor rupture was not a prognostic risk factor.